Potencial da imersão parcial em piscina aquecida como tratamento integrante do controle da hipertensão arterial - Arca, Eduardo Aguilar; Martin, Luis Cuadrado [UNESP]; Martinelli, Bruno; Barrile, Silvia Regina; Franco, Roberto Jorge da Silva [UNESP] (My University, 2012)
Background and objectives: Traditionally, drug therapy is used in the control of high blood pressure (HBP); however, partial immersion baths can be used as constituent therapy in the treatment of hypertensive individuals. The objective of this study was to make a literature review on physiological modifications on cardiovascular, renal and hormonal systems of people with HBP during partial immersion. Contents: Just because the subject remains in rest with water up to chest-neck level in a heated pool, a series of physiological modifications occurs, after some minutes, in the cardiovascular, renal, hormonal, musculoskeletal and central nervous systems. Conclusion: The partial immersion can be an additional therapeutical measure adopted in the control of HBP; however, more research is necessary to support this statement, in order that it can be eventually prescribed by health care professionals and made available for hypertensive individuals.

Justificativa e objetivos: Tradicionalmente a terapia medicamentosa é empregada no controle da hipertensão arterial (HA), contudo, a imersão parcial aquática pode ser utilizada como terapia integrante no tratamento dos hipertensos. O objetivo deste estudo foi realizar uma revisão da literatura a respeito das modificações fisiológicas ocorridas pelos sistemas cardiovascular, renal e hormonal durante imersão parcial em portadores de HA. Conteúdo: Pelo simples fato do indivíduo permanecer em repouso com água ao nível tóraco-cervical em piscina aquecida, após alguns minutos, ocorre uma série de modificações fisiológicas nos sistemas cardiovascular, renal, hormonal, musculoesquelético e nervoso central. Conclusão: A imersão parcial pode ser mais uma medida terapêutica adotada no controle da HA, porém ainda são necessárias mais pesquisas que possam solidificar esta afirmação, para posteriormente ser prescrita pelos profissionais da área da saúde, a fim de disponibilizá-la aos hipertensos.
Potential of partial immersion bath in heated pool as constituent treatment for the control of high blood pressure
Keywords: Cardiovascular physiological phenomena; High blood pressure; Immersion; Fenômenos fisiológicos cardiovasculares; Imersão; Hipertensão arterial